(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: At the time of diagnosis most of pancreatic cancer is in the advanced stage and curative resection becomes impossible. These inoperable diseases are labeled as uresectable carcinonma pancreas. Accurate and early assessment is essential for such patients to gain a better outcome. Objective: This study was carried out to evaluate clinical presentations, laboratory investigations, histopathology and imaging modalities used to diagnose and label pancreatic carcinoma as unresectable. Methods: This retrospective study was carried out from July 2004 to June 2006 in BIRDEM Hospital, Dhaka. After careful scrutiny of clinical presentation, laboratory imaging studies, tissue diagnosis, tumor markers and operative findings it was seen that 50 patients (sample size n = 50) were labeled as unresectable carcinoma pancreas. Male patients were 28 (n1 = 28) and female patients were 22 (n2 = 22). Chi-square (?2) test was applied and P value <0.01 was considered as significant. Result: Most (72%) of the unresectable carcinoma pancreas patients presented with weight loss and obstructive jaundice. Laboratory study and ultrasonography (USG) were carried out in all patients (n = 50). Computerized tomography (CT) scan was done in 45 patients, magnetic resonance imaging (MRI) in 8 patients, endoscopic retrograde cholangiopancreatography (ERCP) in 20 patients and upper gastrointestinal (UGI) contrast was carried out in 10 patients. Preoperative biopsy was taken from 25 patients. Most of the patients presented with abnormal liver functions and raised tumor markers. Three patients had mild renal impairment. USG was able to diagnose 84% patients with pancreatic carcinoma and could delineate features of unresectibility in 69% patients. CT scan diagnosed 90% patients with pancreatic carcinoma and outlined the features of unresectibility in 84.44% patients. ERCP was able to diagnose 13 (65%) patients as carcinoma pancreas but failed to delineate the features of unresectibility in any of the patients. UGI contrast was able to diagnose only 10% unresectable pancreatic carcinoma. MRI was 100% accurate in delineating unresectable carcinoma pancreas. Preoperative tissue diagnosis was 88% sensitive in diagnosing pancreatic carcinoma. Conclusion: Presentation of unresectable carcinoma pancreas was obvious in most cases. Laboratory studies were of great help. Multimodal preoperative imagings were 87.5% accurate in diagnosing unresectable carcinoma pancreas. Tissue diagnosis was important as all the lesions were not pancreatic cancer. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.22 Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 18-24